LEGAL ANALYSIS OF INVESTMENT MANAGEMENT IN EMPLOYMEN SOCIAL SECURITY PROVIDERING AGENCY (BPJS KETENAGAKERJAAN) - Muhamad Hasan Muaziz (AL WASATH Jurnal Ilmu Hukum, 2022)
The social security program as mandated by the Indonesia Constitution is the basic responsibility of the government in terms of providing social protection to its people, with the hope that the Indonesian people will be able to achieve a prosperous life. The goal to be achieved by the government with the establishment of a social security system is to provide certainty of social protection and welfare for all people. The research method used in this research is normative juridical which makes the rule of law a norm. The results obtained from this study are that the financial investment system at BPJS Ketenagakerjaan is based on Rule Number 24 of 2011 concerning the Social Security Administering Body which in general there are three sources of investment in BPJS Ketenagakerjaan, which is a separated state asset. and not divided into shares, the result of the transfer of assets of the State-Owned Enterprises that organize social security programs, the results of the development of BPJS assets. And until now BPJS Ketenagakerjaan also does not have a clear legal instrument to make the basis for making cut loss policies for corporate actions on shares, so so far the management of BPJS Ketenagakerjaan has never taken cut loss actions.